(untitled) (Research, Society and Development, 2022)
Due to the high prevalence of diabetes and its complications, the assessment of patients’ quality of life is essential. Thus, the objective of this research was to review the available literature in an integrative way to clarify aspects related to the quality of life of patients affected by Diabetes Mellitus. This is an integrative literature review study with a qualitative approach and data collection was performed through an active search for information in the electronic databases: Scientific Electronic Library Oline (ScieLO), PubMed and Science Direct. The complications of Diabetes mellitus can be responsible for most of the morbidity and mortality associated with the disease, therefore, evaluating the quality of life of patients at regular intervals is a necessity for Diabetes mellitus as a chronic disease and this evaluation, as a powerful tool, is fundamental. in predicting the status of patients for disease management and long-term health care. In the present review, it was possible to verify that the quality of life of patients with diabetes is affected by numerous factors, such as gender, occupation, history of disease and presence of complications.